An evaluation of talimogene laherparepvec for the treatment of melanoma. (2nd January 2020) - Broman, Kristy K.; Zager, Jonathan S.
ABSTRACT: Introduction : Intralesional therapies have emerged as effective immune therapies for locally advanced and metastatic melanoma. Talimogene laherparepvec (T-VEC), an oncolytic virus derived from the herpes simplex 1 (HSV-1) virus, is the first and only FDA approved intralesional therapy for recurrent, unresectable cutaneous, subcutaneous or nodal metastases from melanoma. Areas covered : We discuss results from clinical trials of T-VEC including data on safety, biodistribution, and viral shedding, which established the current treatment protocol and basis for FDA approval. Data are presented from early implementation of T-VEC in clinical practice. We explore the use of T-VEC in the neoadjuvant setting and in combination with anti-CTLA-4 and PD-1 therapies, including available evidence to support a mechanism for the observed synergistic effect. Expert opinion : Intralesional T-VEC is effective for unresectable stage III and IVa melanoma, with early clinical results comparing favorably to response rates from clinical trials. Clinical applications will likely increase as more data become available on its use in the neoadjuvant setting and in combination with other systemic immune therapies. We expect the fields of intralesional therapy and viral oncotherapy to expand as we better understand how to manipulate the tumor microenvironment and host immune response to cancer.